MEDIA PUZZLE ANGKA SEBAGAI ALTERNATIF UNTUK MENSTIMULASI PERKEMBANGAN KOGNITIF DALAM MENGHITUNG DAN MENGENAL ANGKA PADA ANAK DI SENTRA WIRAJAYA MAKASSAR - Afif, Nur; Firdaus, Faradillah; Nurbaiyana, Nurbaiyana; Aswati, Nurul (Devote: Jurnal Pengabdian Masyarakat Global, 2022)
One of the important developments in the adolescent development stage is cognitive development. Cognitive development is one factor that is intensive enough to be developed in adolescents. This activity aims to stimulate cognitive development in counting and recognizing numbers in children at Sentra Wirajaya Makassar who are still relatively difficult to count and recognize numbers using puzzle media. The implementation method used is pre-experimental with a one shot case study design. There were 10 children participating in this activity. Data collection techniques in this activity use cognitive instruments in ordering numbers. Based on the results obtained, it can be said that games using puzzle media can stimulate children's cognitive development in counting and recognizing numbers in children.